2022
DOI: 10.1021/acs.jproteome.2c00167
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Mononucleotide Administration Restores Redox Homeostasis via the Sirt3–Nrf2 Axis and Protects Aged Mice from Oxidative Stress-Induced Liver Injury

Abstract: Altered adaptive homeostasis contributes to aging and lifespan regulation. In the present study, to characterize the mechanism of aging in mouse liver, we performed quantitative proteomics and found that the most upregulated proteins were related to the oxidation–reduction process. Further analysis revealed that malondialdehyde (MDA) and protein carbonyl (PCO) levels were increased, while nuclear Nrf2 and downstream genes were significantly increased, indicating that oxidative stress induced Nrf2 activation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Therapeutic roles of NMN are generally explained with upregulation of antioxidants to protect cells against redox imbalance. Based on our and other previous reports, the antioxidant function of NMN has been associated with the Nrf2 antioxidant pathway [ 12 , 23 , 24 , 25 , 26 ]. We recently demonstrated that NMN treatment increased Nrf2 expression and cellular protective properties in retinal 661W cells under CoCl 2 -induced pseudohypoxic oxidative stress conditions [ 12 ].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Therapeutic roles of NMN are generally explained with upregulation of antioxidants to protect cells against redox imbalance. Based on our and other previous reports, the antioxidant function of NMN has been associated with the Nrf2 antioxidant pathway [ 12 , 23 , 24 , 25 , 26 ]. We recently demonstrated that NMN treatment increased Nrf2 expression and cellular protective properties in retinal 661W cells under CoCl 2 -induced pseudohypoxic oxidative stress conditions [ 12 ].…”
Section: Discussionmentioning
confidence: 65%
“…Next, as NMN treatment has also been reported to increase antioxidant genes (especially, nuclear factor erythroid-2-related factor 2; Nrf2 ) in various cell types in vitro and in vivo [ 12 , 23 , 24 , 25 , 26 ]. Therefore, we examined whether NMN treatment could increase Nrf2 mRNA expression under our current condition ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…22 In addition, applying nicotinamide mononucleotide, is well known that vitamin B3, to suppress SIRT3/Nrf2 axis could restore oxidoreductive homeostasis and protect liver from oxidative stress-induced injury in mice. 49 Here, we found that SIRT3/ SOD2-mediated ROS accumulation induced the loss of mitochondrial membrane potential and cell death in Pb-stimulated lung cells, indicating that the SIRT3/SOD2 pathway is critical in oxidative damaged mitochondria.…”
Section: Pb(no 3 ) 2 -Induced Oxidoreductive Response Requires Sirt3mentioning
confidence: 65%
“…In a murine model of SIRT3 gene knockout, fibrosis developed in the lungs, liver, and kidneys of mice at 15 months of age 49 . Several previous studies demonstrated a direct regulatory loop between SIRT3 and Nrf2 in various diseases, 50–53 indicating that SIRT3‐Nrf2 loops also exerted its function in LN development. Our results from the RMC and HEK293 cell models concurred with previous findings that SIRT3 upregulation following DEX pretreatment is positively correlated with alleviated inflammation and oxidative stress and reduced cell death.…”
Section: Discussionmentioning
confidence: 98%